Achieving Productivity in the New Normal: Teachers’ Work Productivity in Public Secondary Schools Division of Zambales - de Guzman, Marie Fe D; Blanco, Martha Jelle D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study described the level of teachers’ work productivity em-ployed in the thirteen Districts of DepEd Division of Zambales. The present study was conducted during the third quarter of the school year 2022-2023. The research design is descriptive; quantitative in interpretation using inferential statistics for data analysis; and utilized survey questionnaire as main research instrument. The school heads are male middle aged adults, master's degree holders, and served in the profession for two and a half decades as Princi-pals I and IV. The teachers are female young adults, baccalaureate degree holders with master’s units and served in the teaching pro-fession for a decade as Teacher I. The school heads strongly agreed that the level of teachers’ work productivity was high on school and community engagement primarily taking other roles as teach-er, responsibilities in school, and with colleagues while the teach-ers strongly agreed that the level of their work productivity was high on instructional planning and delivery mostly on identifying the learning objectives and how these can be achieved by the learners. The ANOVA computation revealed a no significant differ-ence in the described level of teachers’ work productivity when grouped according to school head and teacher respondents’ pro-file. An Enhancement Program was designed and proposed aimed to help improve the work productivity of teachers which can po-tentially increase overall school performance and output.